2003
DOI: 10.1093/alcalc/agg013
|View full text |Cite
|
Sign up to set email alerts
|

PLATELET CD62p EXPRESSION AND MICROPARTICLE FORMATION IN MURINE ACQUIRED IMMUNE DEFICIENCY SYNDROME AND CHRONIC ETHANOL CONSUMPTION

Abstract: Elevated platelet CD62p and PMPs may represent a pro-thrombotic status that have important pathological consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Evaluation of MPs levels was performed in citrated whole blood, with the advantage to let the MPs in a physiological environment, without preanalytical steps . Ten μL of citrated blood were diluted with 490 μL phosphate‐buffered saline (PBS); Sigma Chemicals, St Louis, Missouri.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of MPs levels was performed in citrated whole blood, with the advantage to let the MPs in a physiological environment, without preanalytical steps . Ten μL of citrated blood were diluted with 490 μL phosphate‐buffered saline (PBS); Sigma Chemicals, St Louis, Missouri.…”
Section: Methodsmentioning
confidence: 99%
“…Isotype‐matched control antibodies were obtained from Beckman Coulter. PMPs were identified by gating on GPIIb/IIIa (CD41b)‐positive events and distinguished from normal‐sized platelets by forward scatter (FS) size analysis . ErMPs were identified by gating on glycophorin A‐positive events and distinguished from fragmented RBCs by FS size analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction can affect the function and survival of PLTs after transfusion. It has been suggested that CD62P acts as a mediator in the clearance of PLTs in the circulation (33)(34)(35). However, some studies did not agree and stated that despite the binding of PLTs to leukocytes via CD62P, this molecule did not have a role in the clearance of PLTs (36).…”
Section: Discussionmentioning
confidence: 99%
“…The modified Tyrode's buffer [134 mM NaCl, 0.34 mM Na 2 HPO 4 , 2.9 mM KCl, 12 mM NaHCO 3 , 20 mM HEPES, 5 mM glucose, and 0.35% (w/v) bovine serum albumin, pH 7.0] was added to bring the sample volume to 100 l. From these diluted samples, aliquots were placed in 12 ϫ 75-mm polypropylene tubes along with the appropriate antibody, collagen (2.5 g/ml), and the modified Tyrode's buffer in a final volume of 200 l. In vitro experiments, N-coumaroyldopamine and N-caffeoyldopamine were dissolved in ethanol and added to diluted blood samples, where the final ethanol volume never exceeded 0.5% (v/v) in both control and test tubes. Samples were analyzed for P-selectin (CD62p) expression on platelets within 1 h of the collection by flow cytometry (Chen et al, 2003;Nieswandt et al, 2005). Data were acquired for 10,000 platelets, and the extent of exposure of CD62p was determined as the measure of platelet activation (FACSCalibur flow cytometer and Cell Quest Pro software; BD Biosciences, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%